Pengaruh Penambahan Kapur Dan Semen Terhadap Nilai Cbr Tanah Lempung Merah - Ukiman, Ukiman (Politeknik Negeri Semarang, 2013)
Granular of soil as a material supporter of building foundations, heavily influenced by the physical properties of water. Moreover, the fine-grained soil clays in particular, due to water entering the soil particle then inflate and vice versa due to reduced ground water will shrink. Red clay soil stabilization with lime and cement materials, seeks to increase the carrying capacity of the soil as subgrade layer to buffer the load through the foundation component that serves to spread the load on it to buffer the soil section. In addition to the added material lime and cement as filler material also serves as a lasting cementation thus increase the carrying capacity of the red clay soil. Better material cemented its CBR value increase of the lime.